COMPETITIVENESS OF RURAL TOURISM PRODUCT IN RESPONDENTS’ OPINION - Balińska, Agata (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents an issue of competitiveness of rural tourism product. From a tourist’s point of view the competitiveness is largely based on its attractiveness and determined by a number of financial and non-financial aspects. The article presents results of the research conducted among 520 tourists spending their holiday in 14 communes of the eastern borderland of Poland (Szypliszki, Giby, Płaska, Krynki, Dubicze Cerkiewne, Mielnik, Rokitno, Wola Uhruska, Dorohusk, Horodło, Lubycza Królewska, Hrubieszów, Horyniec Zdrój, Radymno). The factors presented in the paper were decisive in terms of high rankig of a tourist product competitiveness in the respondents’ opinion.